Optimal vaccination and control strategies against dengue. (16th April 2019) - Fischer, Anne; Chudej, Kurt; Pesch, Hans Josef
Abstract : This article focuses on the mathematical modelling of a disease outbreak of dengue fever. A cost‐efficient fighting strategy, which simultaneously uses vaccination, application of insecticides to adult and aquatic mosquitoes, and an approach to decrease the number of man‐made breeding places for the mosquitoes, is computed using optimal control. Vaccination includes a paediatric vaccination and an imperfect random mass vaccination with waning immunity.